Procedimentos para a determinação de cádmio para análise de amostras sólidas por espectrometria de absorção atômica com chama (SSA-FAAS) - Costa, Adilson Ben da (2004)
The purpose of this study was to develop a system for solid sampling analysis by flame atomic absorption spectrometry (SSA-FAAS), which would allow the use of higher sample mass when compared to other devices reported in the literature. The proposed system was made in quartz and two sample introduction procedures have been developed: samples were put in paper capsules or it was prepared as pastilles using agar as an agglutinate. Cadmium determination in biological samples was chosen for the demonstration of potential of this system, and calibration procedures was made using biological certified reference materials. Cadmium determination was made using an atomic absorption spectrometer with deuterium background corrector, using an air + acetylene flame, and a singleslot burner. The results were compared to those obtained by electrothermal atomic absorption spectrometry (ET AAS), after acid decomposition of the samples. Better results were obtained with the agar pastille samples. In this case, it was possible to use up to 21 mg of sample with the proposed system. Background signals were always below 0.08. The limit of quantification (LQ) was typically 37 ng g-1, one order of magnitude lower than those reported using other devices for SSA-FAAS. Using samples in paper capsules, the LQ was deteriorated due to the impurity of the paper (LQ = 750 ng g-1). No significant differences (P < 0.05) in the results were observed comparing the proposed procedure and conventional procedures using ET AAS. The sensitivities (based on the characteristic mass) were 0.34 and 0.19 ng using paper capsules and pastille procedures, respectively. The relative standard deviation was below 8%, and no memory effects were observed during the analytically useful lifetime of the quartz cell (ca. 1000 determinations). Thus, the developed system can be proposed for cadmium determination in biological samples by SSA-FAAS.